Effects of chronic disease self-management programs for participants with higher depression scores: secondary analyses of an on-line and a small-group program - Ritter, Philip L (Transl Behav Med, 2014)
Depression often accompanies chronic illness. Study aims included determining (1) the level of current depression (Patient Health Questionnaire (PHQ)-8 ≥ 10) for two sets of Chronic Disease Self-Management Programs (CDSMP) participants; (2) if depression or other outcomes improved for those with PHQ-8 ≥ 10; and (3) if outcomes differed for participants with or without depression. This study utilized longitudinal secondary data analysis of depression cohorts (PHQ-8 ≥ 10) from two independent translational implementations of the CDSMP, small-group (N = 175) and Internet-based (N = 110). At baseline, 27 and 55  % of the two samples had PHQ-8 10 or greater. This decreased to 16 and 37  % by 12  months (p < 0.001). Both depressed and non-depressed cohorts demonstrated improvements in most 12-month outcomes (pain, fatigue, activity limitations, and medication adherence). The CDSMP was associated with long-term improvements in depression regardless of delivery mode or location, and the programs appeared beneficial for participants with and without depression.